Średniowieczne uzbrojenie plebejskie w świetle odkryć archeologicznych, źródeł ikonograficznych i pisanych na ziemiach polskich - Głosek, Marian (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
In the medieval period no doubts are raised on proper classification of three representatives of the offensive armament: sword, spear and dagger (but not battle-knife). They should all be considered knight arms. It is generally assumed that in the late medieval period the plebs’ arms were battle-axes, battle flails, forks and above mentioned bludgeons of all types, spears, halberds, bows, choppers, cutlasses, and as regards protective armament - helmets of capalis and salada types. However, it does not mean that even in the late medieval period these elements of armament were only used by plebs, including also the middle class. Almost all the elements of armament (except battle forks) were also used by knights. In the 2nd half of the 15th century sable comes into use and were also used by the knights. This fact has been noted by chroniclers in a wedding suite of Casimir Jagiellon’s daughter – Jadwiga. This element of armament, in shape not very different from chopper, was also used by the plebs. In the battle of Grunwald in 1410, the knights, after having destroyed their spears, fought with swords and „securibus longius lingo extensis”. Face to face with the king Casimir Jagiellon a tournament duel with battle-axes between Jacob from Kobylany and a famous for tournament victories Englishman of unknown name. At the same time, peasants from Great Poland were called to defend the land from the Teutonic invasion in 1403 and were told to take „cum armis, arcubus, clypeis, lanceis, gladiis et securibus”. Even knights who belonged to the elite were wearing capalis, among others John from Czulice of the Czewoja clan. That is the reason why it is difficult to unambiguously state the class membership of many armament elements, which are nowadays preserved.